2018
DOI: 10.1016/j.pmedr.2018.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Soda intake and tobacco use among young adult bar patrons: A cross-sectional study in seven cities

Abstract: Young adults are among the greatest consumers of sugar sweetened beverages, and they also have high smoking rates. However, few studies address the relationship between these risk behaviors; this study examined the relationship between soda consumption and smoking among young adult bar patrons, a high-risk understudied population. A cross-sectional survey of young adult bar patrons (between January 2014 and October 2015) was conducted using randomized time location sampling (N = 8712) in Albuquerque, NM, Los A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…In all models, the more frequently SSBs were consumed, the association with smoking behaviour strengthened, which aligns with current literature in adults. Kearns and colleagues ( Kearns et al, 2018 ) demonstrated a significant increase in nicotine consumption with increased SSB consumption in a young adult population (mean age: ∼24 years), and in a large American cohort (n = 12,214), SSB consumption predicted smoking behaviour in adults (Age: >18 years) ( Kristal et al, 2015 ). Further, high energy drinks, a sub-class of SSB, are a large source of caffeine in youth ( Branum et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In all models, the more frequently SSBs were consumed, the association with smoking behaviour strengthened, which aligns with current literature in adults. Kearns and colleagues ( Kearns et al, 2018 ) demonstrated a significant increase in nicotine consumption with increased SSB consumption in a young adult population (mean age: ∼24 years), and in a large American cohort (n = 12,214), SSB consumption predicted smoking behaviour in adults (Age: >18 years) ( Kristal et al, 2015 ). Further, high energy drinks, a sub-class of SSB, are a large source of caffeine in youth ( Branum et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…High energy drinks have predicted e-cigarette use and smoking in Finnish adolescents as well ( Kinnunen et al, 2018 ). This may be related to altered taste perceptions in smokers, causing overconsumption of sweeteners ( Kearns et al, 2018 , Pepino and Mennella, 2007 , Sato et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other cross-sectional work has shown a link between SSB and smoking behaviours in adults. In a large American cohort (n = 12,214), nicotine consumption was associated with increased SSB consumption in a young adult population (mean age: ~24 years) [ 46 ]. This was also seen in a general adult population as SSB consumption predicted smoking behaviour [ 47 ].…”
Section: Discussionmentioning
confidence: 99%